Irregular Phonological Marking of Japanese Compounds Benjamin Smith Lyman's Pioneering Research on Rendaku - Vance, Timothy J. (The Mouton-NINJAL Library of Linguistics,, 2022)
Benjamin Smith Lyman (1835-1920) was an American geologist and mining engineer who worked for the Japanese government as a foreign expert in the 1870s. He is famous among linguists for an article about a set of Japanese morphophonemic alternations known as rendaku (sometimes translated as "sequential voicing"). Lyman published this article in 1894, several years after he returned to the United States, and it contains a version of what linguists today call Lyman's Law. This book includes a brief biography of Lyman and explains how an amateur linguist was able to make such a lasting contribution to the field. It also reproduces Lyman's 1894 article as well as his earlier article on the pronunciation system of Japanese, each followed by extensive commentary. In addition, it offers an English translation of a thorough critique of Lyman's 1894 article, published in 1910 by the prominent Japanese linguist Ogura Shinpei. Lyman's work on rendaku included much more than just Lyman's Law, and the final chapter of this book assesses all his proposals from the standpoint of a modern researcher